Evaluation Of Physical Activity Monitor (Pam) On Health And Fitness In Sedentary Individuals - Wong, Sook Kwan (2005)

(untitled)
The purpose of this study was to evaluate the effectiveness of Physical Activity Monitor (PAM) on health and fitness amongst sedentary adults in Kelantan. PAM is a computer system designed to enhance physical activity level and further promote heaithy lifestyle among the sedentary population. 202 sedentary males (M) and females (F) participated in this study. They were randomly assigned into the PAM Intervention group (PAMIM; PAMIF) or Control group (Contro/IM; Contro/IF). All the groups underwent anthropometric, body composition, health and fitness assessments before and after the 3-month programme. Height (HT) and body weight (WT) were measured using a Seca® bodymeter 208 and Tanita® TSF-410 (Japan), respectively. Sody Mass Index (SMI) was then calculated from the HT and WT measurements (WT.Hr2 ). Regression equation for percent body fat (%SF) prediction was used. Waist and hip circumferences were measured, which then determined the Waist-Hip Ratio (WHR) (W.H-1). Tujuan kajian ini adalah untuk menilai keberkesanan Physical Activity Monitor (PAM) mengenai tahap kesihatan dan kecergasan di kalangan orang dewasa yang sedentari di Kelantan. PAM adalah satu sistem komputer pengawalan aktiviti fizikal yang direka untuk meningkatkan tahap aktiviti fizikal dan mempromosi kehidupan sihat di kalangan populasi sedentary. Sejumlah 202 peserta yang terdiri daripada lelaki (M) dan perempuan (F) yang sedentari menyertai kajian ini. Mereka di bahagikan kepada kumpulan PAM (PAMIM; PAMIF) atau Control (Contra/1M; ControllF) secara rawak. Semua kumpulan menjalani ujian-ujian antropometri, komposisi badan, kesihatan dan kecergasan sebelum dan selepas 3 bulan. Ukuran ketinggian (HT) dan be rat badan (WT) telah diambil dengan menggunakan Seca® bodymeter 208 dan Tanita® TBF-410 (Japan). Indeks Jisim Badan (BMI) dikira dengan menggunakan data HT and WT (WT.HT2). Formula regresi untuk peratusan lemak badan (%BF) digunakan. Lilitan pinggang dan punggung diukur, untuk mendapatkan Nisbah Pinggang-Punggung (WHR) (W.H-1).